ON THE IDENTIFICATION TECHNIQUE IN SYSTEM ANALYSIS OF THIN ISLAND FILMS - Psarev, V. I.; Parkhomenko, L. A.; Pyankova, Y. V. (Radio Electronics, Computer Science, Control, 2024)
Analytical formulas for a systemic analysis of the structural coarsening of an island films on a solid substrate are obtained based on a comparison of the characteristics of theoretical and experimental distributions of the islands size. The proposed method provides useful information on the occurrence of various processes in a microislands system as it approaches the equilibrium state.